Inspirations by plant in the decorative motifs of St. Mary’s Basilica in Kraków (Poland) - Brišová, Adriana (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2019)
The aim behind this study was to identify the plants which are the floristic motifs of ornaments inside of Church of Our Lady Assumed into Heaven in Kraków. The art techniques used in ornaments submitted to the analysis were: paintings, sculptures and stained glass-works. The analysis was based on the photographs of various parts of the St. Mary’s Basilica taken between 2017 and 2018. Identified species of plants were presented in the table. In the analysis performed here, the author was focused on the symbolism of chosen floral art motifs, since the artist’s botanical knowledge was not the only inspiration for utilising such decorations. Due to its symbolism, the motif of flowers was commonly used in the religious art, highlighting the dignity and majesty of this beautiful place of worship. Even though the meaning of plants as a symbol often depends on the cultural basis in which the work is done, there are some examples of plants that are widely known as religious symbols by everyone.